PENGEMBANGAN MEDIA PEMBELAJARAN GEOGRAFI BERBENTUK PERMAINAN ULAR TANGGA BERBANTUAN LEAFLET DI SMA DWIJENDRA DENPASAR - Dwisukamsurya, P.Md.Desy; Lasmawan, I Wayan; Sriartha, I Putu (Universitas Pendidikan Ganesha, 2019)
This research aimed to develop geography learning media in the form of snake ladder game assisted by leaflet, analyzing the effectiveness to activity and students learning achievement. This research used development (R&D) research design with analysis, design, development, implementation, evaluation (ADDIE). The students learning activity data were collected through observation, besideds, the students learning achievement were collected through multiple choice test. The data collected then analyzed descriptively and quantitatively. The final design of geography learning media in the form of snake ladder game assisted by leaflet was geography learning media based on the evaluation : 1) material and media expert valid average score 3,18; 2) small grup trials valid average score 3,69 the data were reasonably used. The geography learning media in the form of snake ladder game assisted by leaflet effectively improved the learning activity equal to 15,36% and effectively improved the students learning achievement with the level of completeness of student learning achievement at 91,43% with fine category.